The Riddle of Parmenides - Saulius, Tomas (Problemos, 2009)
Parmenides of Elea is a Janus-faced historical personage; his only known treatise On Nature may be characterized as a fusion of heterogeneous elements or even direct opposites: here, vivid poetical metaphors are inextricably intertwined with the most abstract categories of “pure reason” (i.e. being and nonbeing), trivial truths – with irresolvable paradoxes; the so-called “Way of Opinion”, which runs through the sensible world, intertwines with the dialectical “Way of Truth” which leads to the ultimate reality. Are ambiguity and duality only accidental features of the poem? Traditionally, the doctrine of “being” is treated as a “content” which can be isolated from the “form” or “mode of expression.” The article shows that such methodological premise is far from being self-evident and unquestionable.